2006
DOI: 10.1177/0091270006288954
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Aprepitant on Hydrodolasetron Pharmacokinetics in CYP2D6 Extensive and Poor Metabolizers

Abstract: To prevent chemotherapy-induced nausea and vomiting, aprepitant is given with a corticosteroid and a 5-hydroxytryptamine type 3 antagonist, such as dolasetron. Dolasetron is converted to the active metabolite hydrodolasetron, which is cleared largely via CYP2D6. The authors determined whether aprepitant, a moderate CYP3A4 inhibitor, alters hydrodolasetron pharmacokinetics in CYP2D6 poor and extensive metabolizers. Six CYP2D6 poor and 6 extensive metabolizers were randomized in an open-label, crossover fashion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…11,12 Aprepitant also induces CYP2C9 24,26,29 but, unlike rolapitant, does not inhibit CYP2D6. 30 To date, the drug-interaction potential of netupitant is restricted to studies on the CYP3A family, with respect to which netupitant is a moderate inhibitor of CYP3A. 25 IV rolapitant 166.5 mg was well tolerated when coadministered with cocktail probe drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Aprepitant also induces CYP2C9 24,26,29 but, unlike rolapitant, does not inhibit CYP2D6. 30 To date, the drug-interaction potential of netupitant is restricted to studies on the CYP3A family, with respect to which netupitant is a moderate inhibitor of CYP3A. 25 IV rolapitant 166.5 mg was well tolerated when coadministered with cocktail probe drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both a single dose of IV fosaprepitant and a 3‐day oral aprepitant regimen require a reduction in dexamethasone dose . Aprepitant also induces CYP2C9 but, unlike rolapitant, does not inhibit CYP2D6 . To date, the drug‐interaction potential of netupitant is restricted to studies on the CYP3A family, with respect to which netupitant is a moderate inhibitor of CYP3A …”
Section: Discussionmentioning
confidence: 99%
“…All adverse events were mild or moderate in intensity, and all events resolved. The ECG effects of hydrodolasetron are dose dependent and were reported to be observed at single doses greater than 200 mg [ 19 ]. Since the recommended oral dose of dolasetron of 100 mg was utilized in the present study, increase in plasma concentration of up to twofold or 100% (equal to a 200-mg dose) can be considered clinically unimportant for the 100-mg dose.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no effect on cardiac function of casopitant coadministered with the serotonin antagonist ondansetron was recently reported [ 15 ]. Further, Li et al [ 19 ] have reported that there is no effect of a similar NK-1 receptor antagonist, aprepitant, on the PK and cardiac safety profile of hydrodolasetron in CYP2D6 EMs or PMs. Consequently, these findings, coupled with no clinically important increase in hydrodolasetron or granisetron exposure in the presence of casopitant, suggest that casopitant is unlikely to increase the potential for either of these drugs to elicit life-threatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation